PENGARUH KEPEMILIKAN INSTITUSIONAL, PERTUMBUHAN ASET DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI INTERVENING VARIABLE (STUDI PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI PERIODE 2009-2013) - Ningsih, Endang Setya; Efni, Yulia; Halim, Edyanus Herman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to know the effect of institutional ownership directly and indirectly, asset growth and profitability mediated by the dividend policy to firm value in the LQ-45 companies listed in Indonesia Stock Exchange in the period of 2009-2013.There were 45 companies in this study that become the population LQ-45 and the sample consisting of 20 companies with the number N of data as much as 100. The sampling technique is based porposive sampling. Analysis of the data use descriptive analysis and path analysis. The founding indicates that institutional ownership has no significant effect on dividend policy directly, asset growth does not effect significant to the direct dividend policy, the profitability brings significant effect to firm value directly, institutional ownership has no significant effect on firm value directly. In addition, Asset growth does not significantly influence to the value of the company directly, profitability effects significantly to the value of the company directly and then dividend policy effects significantly to the firm value directly. This means that the dividend policy is only able to mediate the relationship between profitability on firm value.Keywords: institutional ownership, asset growth, profitability, dividend policy and firm value.